KEBAKARAN HUTAN DAN LAHAN DI KALIMANTAN TAHUN 2019 (Refleksi atas Globalisasi dan Reduksi Kewenangan Pemerintah) - Safa Muzdalifah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2020)
This article explores the influence of globalization to government authority a case study is Forest and Land Fires in Kalimantan 2019. This study as a verivicative research of the literature review, in order that the results are accept or ignore the thesis. The Result of this research is globalization has a close relation to government authority reduction, since the government disable to achieve the development economic target independently. This resutls proven by the exist of the regulation that increase the foreign investor come in to Indonesia and manage the strategic economics sector. Key Words: Globalization, Government Authority, Forest and Land Fire, Kalimantan